An in vitro study to compare coatings of peptide and collagen on hydroxyapatite coated titanium surfaces / Mohsin Nazir - Mohsin, Nazir (2017)
Introduction: There is a paradigm shift in implantology in recent times. From implants being classically inert, and unable to interact with their environment, to them being biomimetic with the ability to affect their surroundings. Implants and more importantly, their surfaces, nowadays are designed to mimic nature. Therefore, the aim of this study was to compare the cell morphology, proliferation and differentiation of hydroxyapatite (HA) coated titanium surfaces biofunctionalized with RGD, and Collagen. Objectives: The first objective of the study was to modify the surface of the implant by gritting, sandblasting, and acid-etching the CPTi surfaces so that they are comparable to the commercially available implant surfaces. The second objective was to coat the modified surfaces with HA using a Simulated Body Fluid (SBF) solution so that a uniform layer of HA is formed on top of the samples. The third objective was to use physical adsorption for functionalizing RGD and Collagen on the HA/Tricalcium Phospahte coated CPTi surfaces. The final objective was to use the HA/Tricalcium Phosphate as the control to compare the in vitro response on the samples using human osteoblasts. Methods: There were three phases to this experiment, namely, the surface modification phase where gritting, sandblasting, and acid etching took place. The surface characterization phase, where the CPTi samples were coated with hydroxyapatite (HA) with simulated body fluid (SBF), RGD and collagen. The last phase was the in vitro phase where cell morphology, cell viability, cell proliferation and mineralization were assessed using human osteoblast cells (HOB) for the three different groups of surface coatings. Results and Discussion: The sandblasted samples showed an average roughness (Sa) value of 2.48 ± 0.74µm. The acid-etched samples displayed a lesser roughness than their sandblasted counterparts, that is, an average Sa of 2.35 ± 0.18µm. Within the HA/Tricalcium phosphate coated samples, there was a general increase in